Putin's Russia in DER SPIEGEL before 9/11/2001 - Topics and Tendencies - Fuchs, Klaus (Respectus Philologicus, 2003)
One among the most influential of Germany’s print media, the weekly magazine DER SPIEGEL and its editor-in-chief Rudolf Augstein have traditionally taken a very marked interest in Russian affairs. This paper presents an analysis of the magazine’s coverage of Russian politics and society during the first nine months of 2001, i. e. before Muslim fundamentalist terrorism led to a reassessment of Russia’s role and image on the world stage. For this quantitative and qualitative analysis of topics and the image of each topic an original system of evaluation was developed, the purpose of which is to trace stereotypes on Russia in German public opinion as reflected in the country’s media.
Keywords: Russia; politics and society; image; cultural borders